Behavioral Problems in Turkish Preschool-Age Children - (:unkn) unknown (SAGE Publications Ltd, 2010)
To diagnose behavioral problems in preschool children, and to look for an appropriate solution, is vital to prevent the problem from becoming permanent and insoluble. Teachers, working in preschool education institutions, need some instruments to diagnose behavioral problems of their students in order to help them and their parents. In this study, a scale ‘Preschool Behavior Questionnaire’ (Behar, 1976), was adapted into Turkish as ‘Okul Oncesi Davranis Sorunlari Tarama Olcegi’. The scale, considered valid and reliable, was applied to 654 children in the age group of 3–6 by 56 preschool teachers. This scale consists of 30 items and 3 factors. According to the results, the most frequently encountered problem among the young children appears to be “aggressive” behavior, and these behavioral problems vary with gender, age and socio-economic environment. To look for a shared solution with the parents after evaluating preschool children through various methods and instruments was thought to be appropriate. © 2010 A B Academic Publishers Printed in Great Britain.